Modified Surgical Treatment for Achilles Tendon Rupture Secondary to Insertional Achilles Tendinopathy Using Midline Dorsal Approach - Naik, Nagesh; Rahate, Vaijanath; Ghorpade, Kapil R.; Patil, Jaydeep; Patil, Shantanu (Faculty of Medicine Universitas Padjadjaran, 2024)
Objective: To assess the pain relief and functional outcomes of patients who undergo surgical management of Achilles tendon rupture secondary to insertional Achilles tendinopathy and associated conditions using a midline dorsal approach.Methods: This prospective observational study included 30 patients diagnosed with Achilles tendon rupture secondary to insertional Achilles tendinopathy. This study recorded risk factors, predisposing factors, and co-morbidities for all cases. Pain relief and functional improvement were assessed by comparing Visual Analogue Scale (VAS) scores and American Orthopedic Foot and Ankle Score (AOFAS) at the time of presentation and at the final follow-up. This study conducted statistical analysis using SPSS 21.0 software, with a significance level of p<0.05.Results: Of the participants, 17 (56.67%) were male and 13 (43.13%) were female, resulting in a male-to-female ratio of 1:0.76. The mean age of male and female patients was comparable (p=0.7515). The majority of patients (60%) were overweight, while 9 (30%) were obese, and 3 (10%) had a normal body mass index. This study observed a significant reduction in pain and functional improvement in the studied cases, as evidenced by a statistically significant reduction in VAS scores and improvements in AOFAS. Eight (26.66%) patients experienced minor complications that could be managed conservatively, but no major complications were observed.Conclusion: Modified surgical treatment of Achilles tendon rupture secondary to insertional Achilles tendinopathy using a midline dorsal approach leads to significant improvements in pain and functional outcomes, with an acceptable complication rate.